2007
DOI: 10.1097/mbc.0b013e32809cc922
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and thrombophilic risk factors in patients with retinal artery occlusion

Abstract: This article evaluates the prevalence of cardiovascular and thrombophilic risk factors in patients with retinal artery occlusion. Forty-one patients with a first episode of a retinal artery occlusion underwent complete ophthalmic examination, routine blood testing and specific laboratory tests for thrombophilia, such as fasting and postmethionine homocysteine, lipoprotein(a), plasminogen activator inhibitor-1, factor VIII, factor V Leiden, factor II G20210A polymorphism, lupus anticoagulant and anticardiolipin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 46 publications
2
28
0
3
Order By: Relevance
“…Mutation of MTHFR was also examined but no significant association could be found. Other notable studies 46,47 have reported similar findings and population based analysis from the Blue Mountains Eye Study also suggests HHcy and retinal artery emboli are weakly associated. 48 A small meta-analysis 49 suggests HHcy is more common in retinal artery occlusion but again no correlation with MTHFR mutation was found.…”
Section: Retinal Artery and Vein Occlusionsupporting
confidence: 62%
“…Mutation of MTHFR was also examined but no significant association could be found. Other notable studies 46,47 have reported similar findings and population based analysis from the Blue Mountains Eye Study also suggests HHcy and retinal artery emboli are weakly associated. 48 A small meta-analysis 49 suggests HHcy is more common in retinal artery occlusion but again no correlation with MTHFR mutation was found.…”
Section: Retinal Artery and Vein Occlusionsupporting
confidence: 62%
“…Patients with retinal vascular occlusions often present to general practitioners or ophthalmologists, and have previously been associated with various cardiovascular risk factors [7][8][9][10][11][12][13], cerebral microembolisms [14], and cardiovascular events, including stroke and myocardial infarction [11,[15][16][17]. However, another study found that risk factor prevalence differed somewhat between patients with retinal and cerebral ischemia, indicating that there might be pathogenetic differences between retinal and cerebral ischemia [18].…”
Section: Introductionmentioning
confidence: 96%
“…Arterial hypertension, diabetes mellitus, dyslipidemia, or vasculitis number among the risk factors that have been implicated in the development of RAO, but what role thrombophilic disorders might play remains unclear. Anecdotal reports do, however, suggest that an association with CRAO and BRAO [7,8,9,10,11,12] may well exist. Research to date has been unable to verify explicitly suggestions that thrombophilic disorders play a causative role.…”
Section: Introductionmentioning
confidence: 99%
“…Several cross-sectional studies have sought to estimate the prevalence in patients with RAO of systemic diseases that might predispose to in situ thrombosis [6,7]. Arterial hypertension, diabetes mellitus, dyslipidemia, or vasculitis number among the risk factors that have been implicated in the development of RAO, but what role thrombophilic disorders might play remains unclear.…”
Section: Introductionmentioning
confidence: 99%